Fomentación cultural y tradicional de las distintas representaciones de plazas y mercados del cantón Saquisilí, mediante material audiovisual - Yupa Palacios, Luis Fernando (2016)
Plazas and markets are part of the cultural recognition in society, same as with the passage of time have transformations. The plazas and markets of Saquisilí Canton located in the province of Cotopaxi are no exception as the Plaza de Rastro, Plaza Gran Colombia, Plaza Kennedy, Plaza 18 de Octubre, Plaza San Juan Bautista, Plaza de Hierbas, Plaza Vicente Rocafuerte through of the years they have adapted in the environment being beneficial to some and hurtful to others, and in this case of the 7 plazas and markets can be hurtful to people who still maintain the tradition and customs that the ancestors gave over as a legacy. In don´t know however to the promotion of these places there is a on the same, people are don´t know of the importance of that might have them. The audiovisual genre is a way to show what happens in a particular item, previously do a thorough investigation, showing the cultural transformation of each plaza and market.